Core-template-free synthesis of molecularly ethane-bridged hollow mesoporous silica spheres from acid-hydrolyzed precursor. (7th August 2020) - Sun, Yangyi; Mao, Yijing; Di, Ningyu; Chen, Xiaolong; Qi, Dongming; Shentu, Baoqing
Abstract : Molecularly ethane-bridged hollow mesoporous silica spheres with radial mesochannels and enlarged pore size were synthesized by a core-template-free method only through using acid-hydrolyzed TEOS/bis(triethoxysilyl)ethane (BTEE) as precursor. Abstract : Herein, using an acid-hydrolyzed tetraethyl orthosilicate (TEOS)/bis(triethoxysilyl)ethane (BTEE) mixture as a precursor for the traditional surfactant-assembly synthesis of mesostructured silica spheres instead of directly purchased commercial precursors, molecularly ethane-bridged hollow mesoporous silica spheres (MEB-HMSs) with radial mesochannels and an enlarged pore size were successfully synthesized without any additional core templates. The composition, pore size, particle size, shell thickness, and rate could be controllably tailored by only changing the amount of reagents used in the reaction. The cytotoxicity assay confirmed that MEB-HMSs have good biocompatibility, together with good Dox-loading capacity.